2015
DOI: 10.18632/oncotarget.3300
|View full text |Cite
|
Sign up to set email alerts
|

Multiple myeloma induces Mcl-1 expression and survival of myeloid-derived suppressor cells

Abstract: Myeloid-derived suppressor cells (MDSC) are contributing to an immunosuppressive environment by their ability to inhibit T cell activity and thereby promoting cancer progression. An important feature of the incurable plasma cell malignancy Multiple Myeloma (MM) is immune dysfunction. MDSC were previously identified to be present and active in MM patients, however little is known about the MDSC-inducing and -activating capacity of MM cells. In this study we investigated the effects of the tumor microenvironment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 45 publications
5
64
0
Order By: Relevance
“…In contrast to these findings, soluble factors secreted by MM cells increased the viability of both MDSC subsets, especially PMN-MDSCs, in vitro . Similar observations were made by De Veirman et al who showed that conditioned medium from 5T33MM cells increased the viability of total MDSCs [19]. …”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…In contrast to these findings, soluble factors secreted by MM cells increased the viability of both MDSC subsets, especially PMN-MDSCs, in vitro . Similar observations were made by De Veirman et al who showed that conditioned medium from 5T33MM cells increased the viability of total MDSCs [19]. …”
Section: Discussionsupporting
confidence: 87%
“…Our results suggest that PMN-MDSCs could be mobilized from the BM into peripheral blood in the 5TGM1 model, whereas in the MOPC315.BM model these cells remain inside the BM. A recent report showed similar data, with a transient MO-MDSC expansion and a final increase in PMN-MDSCs (end-stage disease) in peripheral blood of C57BL/ KaLwRij mice bearing the 5TGM1-parental 5T33 myeloma [19]. However, in our study some intermediate time points included a relatively small number of animals (N=4) and need confirmation in future studies.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This is further supported by the observation that STAT3 prolongs the binding of C/EBPβ on the myc promoter [76]. Besides myc, other cell survival and cell cycle regulating proteins like Bcl-xL, survivin, Mcl-1 and cyclin D1 are upregulated by STAT3 [6], [31], [80]. STAT3 was further linked to proteins like S100A [81] and protein kinase C βII [82], which inhibit DC differentiation from myeloid progenitor cells and thereby promote MDSC accumulation.…”
Section: Signal Transducer and Activator Of Transcription 3 Plays A Rmentioning
confidence: 82%